FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PADA KKP PRATAMA MAJALAYA - Lasmana, Andy; Wiryanti, Dea Azmi (Universitas Djuanda, 2017)
This research was intended to analyze the effect of sunset policy, tax amnesty, and good governance on taxpayer compliance in Majalaya primary tax office. The population in this study are all registered taxpayer (corporate and individual taxpayer) in Majalaya primary tax office. The number of samples in this study amounted to 110 respondents. Sampling was done using probability sampling methods. Method of data analysis used in this research was by using validity test, reliability test, classic assumption test, multiple regression analysis, the coefficient of correlation, the coefficient of determination (R2 test), F-test, and t-test. Based on researches results, it can be concluded that simultaneously sunset policy, tax amnesty and good governance have an effect on taxpayer compliance. While partially, sunset policy and tax amnesty hasn’t effect on taxpayer compliance, different from good governance which have positive and significant impact to taxpayer compliance.Keywords : sunset policy, tax amnesty, good governance, dan tax compliance